Dinamika Amonium dan Nitrat Lahan Sawah Latosol pada Budidaya Konvensional Padi Lokal dan Hibrida di Subak Jatiluwih - PERMATASARI, GITA YUNI; KESUMADEWI, ANAK AGUNG ISTRI; SUWASTIKA, ANAK AGUNG NGURAH GEDE (Agrotrop : Journal on Agriculture Science; Vol 9 No 2 (2019)DO - 10.24843/AJoAS.2019.v09.i02.p04, 2019)
Ammonium Dynamics and Latosol Wetland Nitrates in Conventional Cultivation of Local and Hybrid Rice in Jatiluwih Subak. Plants absorb nitrogen in the form of ammonium (NH4+) and nitrate (NO3-). Each sample was analyzed for its ammonium and nitrate levels using macro Kjeldahl method. The results showed that the concentration of ammonium and nitrate in soil of the two rice fields were similar. The ions contents were as following: nitrate (2,67%) and ammonium (2,67%) in local rice, while those in hybrid rice fields were amounted of 1,48% and 4,59% respectivelly. The concentration of ammonium and nitrate on 21 DAC in soil samples remained low and rose at 28 DAC, then decreased at 56 DAC. It means that the times of fertilizing always done by the farmers were not appropriate.The content of ammonium and nitrate in water phase much lower than that in soils for both types of rice plants. The highest concentration of ammonium in local rice fields was 0,093% at the time of tillage and the lowest 0% on 21 DAC, while the highest nitrate concentrations in local rice water was 0,37% at 70 DAC and the lowest was 0% at of 21 DAC. The highest ammonium concentrations in hybrid rice 0,33% at 14 DAC, and the lowest 0% at 42 HST, while the highest nitrate content 0,47% at 42 DAC and the lowest 0% at the time of tillage. The fertilizing times recommended based on the findings of this reaserch is at 10-15 DAC for both rice types and another subsquent fertilization on 60-65 DAC for local rice and 40-45 DAC in hybrid rice.